Economics of Space and Time Scientific Papers of Tönu Puu - Andersson, Ake E.; Beckmann, Martin; Löfgren, Karl-Gustaf; Stenberg, Anders (Springer Berlin Heidelberg, 1997)
This book contains a sample of Professor Tönu Puu's contributions to economic theory. The topics range from seminal results on investment criteria under imperfect capital markets and rules for optimal resource extraction when the grade of the ore is heterogeneous, to applications of modern nonlinear dynamics to well-known economic fields like business cycle analysis and oligopoly theory. Puu's thinking on cultural economics and his views on the methodology of economic science are also luckily exposed by the papers in this volume. Readers interested in the spatial dimension of the economy will find original ideas on the optimal allocation of road capital